Comparative Study of Techniques in the Diagnosis of Mycoplasma Pneumonia among the Patients of Respiratory Tract Infections in Northern Indian Population (Global Journal of Medical Research, 2015)
Abstract not found
Keywords: mycoplasma pneumonia; culture; serology; PCR